Policy and governance reforms in Waqf's administration : addressing legal fragmentation and institutional overlaps in Malaysia's legal framework - Wan Muhammad, Ramizah; Abas, Afridah; Laeba, Muhammad; Ibrahim, Norliah (Ahmad Ibrahim Kulliyyah of Laws, IIUM, 2025)
Based on the above discussion it is recommended that the highest Islamic authority at the federal level that is National Council of Islamic Religious Affairs, Malaysia (MKI) to advise and recommend the State Islamic Religious Council to sit together and try to standardize the waqf management and its administration in their respective states as well as any other related issues mentioned above. It is also significant to advise the state governments which are yet to have specific enactment on waqf to legislate the laws in order to improve the administration of waqf in their respective states.